2016
DOI: 10.5392/jkca.2016.16.05.612
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Problem Solving Ability, Critical Thinking Disposition, Creativity, Self Efficacy and Nursing Process Competence of Nursing Students

Abstract: The purpose of this study was to identify the relationship between problem solving ability, critical thinking disposition, creativity and nursing process competence of nursing students. The participants in the study were 246 nursing students enrolled in 2nd year of a BSN program in S city, Korea. Data were collected from June 10 to June 20, 2015 using a structured questionnaire. Relationship between general characteristics and solving ability, critical thinking disposition, creativity and nursing process compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The degree of critical thinking disposition of nursing students was three points on average in this study, which could be interpreted as a moderate level. This is similar to findings of previous studies [14,15,28], which reported that nursing students' average level of critical thinking disposition was three out of a total of five points. Critical thinking is a concept suggested in the standards for accreditation of the Korean nursing curriculum, and is actually one of the concepts used by many nursing colleges as educational outcomes [29,30].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The degree of critical thinking disposition of nursing students was three points on average in this study, which could be interpreted as a moderate level. This is similar to findings of previous studies [14,15,28], which reported that nursing students' average level of critical thinking disposition was three out of a total of five points. Critical thinking is a concept suggested in the standards for accreditation of the Korean nursing curriculum, and is actually one of the concepts used by many nursing colleges as educational outcomes [29,30].…”
Section: Discussionsupporting
confidence: 91%
“…While critical thinking is an important competency for nursing students, the level of critical thinking disposition of nursing students is insufficient in reality. Yang and Sim [14] reported that nursing students who chose their major based on their aptitude or who were highly satisfied with their major had a high tendency to think critically. In this study, only 22.1% of the participants chose their major in consideration of their aptitude, while 71.2% of the participants chose nursing as their major considering employment opportunities or due to the recommendation of an acquaintance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, while Özenç (2012) examined the relationship between functional literacy and academic achievement, Özenç and Dikici (2016) examined the relationship between functional literacy and metacognitive awareness, and Tezel and Tezgören (2019) examined the relationship between scientific literacy and problem-solving skills of 8th-grade students. Furthermore, many studies are examining the relationship of problem-solving skillswith different variables (Saygılı, 2000;Özsoy, 2005;Salami & Aremu, 2006;Sharifi, 2006;Berkant & Eren, 2013;Yang & Sim, 2016. On the other hand, there is no study investigating the relationship between functional literacy and problem-solving skills.…”
Section: Introductionmentioning
confidence: 99%